Ergosta-7,9(11),22-trien-3β-ol Attenuates Inflammatory Responses via Inhibiting MAPK/AP-1 Induced IL-6/JAK/STAT Pathways and Activating Nrf2/HO-1 Signaling in LPS-Stimulated Macrophage-like Cells - Yi-Ping Huang; Dar-Ren Chen; Wen-Jen Lin; Yu-Hsien Lin; Jiann-Yeu Chen; Yueh-Hsiung Kuo; Jing-Gung Chung; Te-Chun Hsia; Wen-Tsong Hsieh (MDPI AG, 2021)
Chronic inflammation induces autoimmune disorders and chronic diseases. Several natural products activate nuclear factor erythroid 2-related factor 2 (Nrf2) signaling, attenuating inflammatory responses. Ergosta-7,9(11),22-trien-3β-ol (EK100) isolated from Cordyceps militaris showed anti-inflammatory and antioxidative activity, but those mechanisms are still unclear. This study is the first to investigate EK100 on antioxidant Nrf2 relative genes expression in LPS-stimulated macrophage-like cell lines. The results showed that EK100 reduced IL-6 (interleukin-6) and tumor necrosis factor-α production. EK100 also attenuated a mitogen-activated protein kinase/activator protein-1 (MAPK/AP-1) pathway and interleukin-6/Janus kinase/signal transducer and activator of transcription (IL-6/JAK/STAT) pathway in LPS-stimulated cells. Toll-like receptor 4 (TLR4) inhibitor CLI-095 and MAPK inhibitors can synergize the anti-inflammatory response of EK100 in LPS-stimulated cells. Moreover, EK100 activated Nrf2/HO-1 (heme oxygenase-1) signaling in LPS-stimulated murine macrophage-like RAW 264.7 cells, murine microglial BV2 cells, and human monocytic leukemia THP-1 cells. However, Nrf2 small interfering RNA (Nrf2 siRNA) reversed EK100-induced antioxidative proteins expressions. In conclusion, EK100 showed anti-inflammatory responses via activating the antioxidative Nrf2/HO-1 signaling and inhibiting TLR4 related MAPK/AP-1 induced IL-6/JAK/STAT pathways in the LPS-stimulated cells in vitro. The results suggest EK100 acts as a novel antioxidant with multiple therapeutic targets that can potentially be developed to treat chronic inflammation-related diseases.